2018
DOI: 10.26553/jikm.2018.9.1.41-52
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Resiko Dan Angka Kejadian Berat Badan Lahir Rendah (Bblr) Di Rsup Dr. Mohammad Hoesin Palembang Tahun 2014

Abstract: Latar Belakang: Berat Badan Lahir Rendah (BBLR) sampai saat ini masih menjadi masalah kesehatanmasyarakat yang utama. Tingginya angka kejadian BBLR dapat mempengaruhi kualitas sumber dayamanusia di masa depan, karena bayi yang lahir dengan BBLR juga dapat menyebabkan peningkatan risikokecacatan permanen, gangguan kognitif dan masalah kesehatan kronis lainnya dikemudian hari. Identifikasifaktor risiko BBLR adalah penting dalam menengahi konsekuensi kesehatan BBLR setelah lahir dan jugadalam mengurangi angka kej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
2
2
4
Order By: Relevance
“…However, the results of the study are not in line with the research by Handayani, Fitriani and Lestari (2019) which found that there was a significant correlation between parity and the incidence of LBW in the Wates Health Center area of Kulon Progo Regency with a large p(sig)=0.037 [25]. according to statistics, mothers who have parity or the number of deliveries > 4 times will tend to increase the risk of experiencing complications in pregnancy [26]. 4.6 The Correlation between Pregnancy Distance and Low Birth Weight (LBW) Infants.…”
Section: The Correlation Of Comorbid Disorders (Anemia and Preeclampsia) To The Incidence Of Low Birth Weight Babies (Lbw)contrasting
confidence: 77%
“…However, the results of the study are not in line with the research by Handayani, Fitriani and Lestari (2019) which found that there was a significant correlation between parity and the incidence of LBW in the Wates Health Center area of Kulon Progo Regency with a large p(sig)=0.037 [25]. according to statistics, mothers who have parity or the number of deliveries > 4 times will tend to increase the risk of experiencing complications in pregnancy [26]. 4.6 The Correlation between Pregnancy Distance and Low Birth Weight (LBW) Infants.…”
Section: The Correlation Of Comorbid Disorders (Anemia and Preeclampsia) To The Incidence Of Low Birth Weight Babies (Lbw)contrasting
confidence: 77%
“…This sensitization process is related to the severity of the disease. 30 Nonetheless, in this study, it was found that all respondents affected by OCD whose severity had been assessed had no effect on their atopic history. This finding is in line with previous research.…”
Section: Discussioncontrasting
confidence: 51%
“…The aims include preventing adverse birth outcomes, low birth weight, and detecting pregnant women who are at risk of giving birth to LBW babies by scoring. Many references state that pregnant women with anemia tend to give birth to LBW babies, but so far there has been no tool or scoring used to determine that pregnant women with a certain score are more at risk of giving birth to LBW babies (Kumalasari, Tjekyan and Zulkarnain, 2018). Through the development of this LBW early detection card, LBW births can be predicted more optimally (Utami et al, 2023).…”
Section: Discussionmentioning
confidence: 99%